Hubungan antara Prestasi Belajar dan Kemampuan Membaca Kritis - Nani Angraini; Tri Riya Anggraini (LPPM STKIP PGRI Bandar Lampung, 2025)
Critical reading skills are very important for learning Indonesian because they help students understand, evaluate, and reflect on texts comprehensively. The purpose of this study was to determine how critical reading skills and learning achievement are related to each other. This study was conducted quantitatively using a correlational approach. A critical reading test was used as the research tool. The results of the Pearson Product Moment correlation test were used to analyze the data. The results showed a significant relationship between critical reading skills and learning achievement, with a correlation value of r = 0.68 and a significance level of α = 0.05. This indicates that the relationship between the two is strong and positive, so that students' learning achievement is positively correlated with their critical reading skills.